Shotgun metagenomic sequencing reveals skin microbial variability from different facial sites - Wei, Qingzhen; Li, Zhiming; Gu, Zhenglong; Liu, Xiao; Krutmann, Jean; Wang, Jiucun; Xia, Jingjing (Frontiers in Microbiology, 2022)
Biogeography (body site) is known to be one of the main factors influencing the composition of skin microbial community. However, site-associated microbial variability at a fine-scale level was not well-characterized, especially there was a lack of high-resolution recognition of facial microbiota across kingdoms by shotgun metagenomic sequencing. To investigate the explicit microbial variance in the human face, 822 shotgun-metagenomic sequencing data from Han Chinese recently published by our group, in combination with 97 North American samples from NIH Human Microbiome Project (HMP), were re-assessed. Metagenomic profiling of bacteria, fungi, bacteriophages, as well as enriched function modules from three facial sites (forehead, cheek and the back of the nose), were analyzed. The results revealed that skin microbial features were more alike in the forehead and cheek while varied from the back of the nose in terms of taxonomy and functionality. Analysis based on biogeographic theories suggested that neutral drift with niche-selection from host could possibly give rise to the variations. Of note, the abundance of porphyrin-producing species, i.e. C. acnes, C. avidum, C. granulosum and C. namnetense, were all the highest in the back of the nose compared to the forehead/cheek, which was consistent with the highest porphyrin level on the nose in our population. Sequentially, the site-associated microbiome variance was confirmed in American populations; however, it was not entirely consistent. Furthermore, our data revealed correlation patterns between P. acnes bacteriophages with genus Cutibacterium at different facial sites in both populations, however, C. acnes exhibited a distinct correlation with P. acnes bacteriophages in Americans/Chinese. Taken together, in this study, we explore the fine-scale facial site-associated changes of skin microbiome and provide insight into the ecological processes that underlying facial microbial variations.